UJI FITOKIMIA DAN UJI TOKSISITAS EKSTRAK KULIT KAYU TERAP (Artocarpus odoratissimus Blanco.) DENGAN METODE BSLT (BRINE SHRIMP LETHALITY TEST) - Yoarga Arsindho; Erwin Erwin; Irawan W Kusuma (PROSIDING SEMINAR KIMIA, 2017)
The phytochemical tests and toxicity test extract from stem bark of terap (Artocarpus odoratissimus Blanco) have been researched. The method used is Brine Shrimp Lethality Test (BSLT), the ethanol and n-hexane extract of this bark terap (A. odoratissimus) were tested. The results showed that the secondary metabolic component from terap (A.odoratissimus)was toxic. The LC50 from the extract of terap (A. odoratissimus) that dissolved in Ethanol was 82.0008 and The LC50 from the extract of terap (A.odoratissimus) that dissolved in n-Hexane was 383.3533 Keywords:Artocarpus odoratissimus, BSLT (Brine Shrimp Lethality Test), LC50